The influence of socio-economic status on the prevalence of food sensitisation and food allergy in children 12 to 36 months in urban Cape Town, South Africa - Hobane, Lelani (Department of Public Health and Family Medicine, 2017)
Background: Globally, food allergies (FAs) have become a public health concern with research suggesting a rising prevalence. FAs affect both the individual and their family advocating for a need to understand the extent of the problem. Allergies have increasingly been recognised as diseases of life-style resulting from interaction between genes and the environment in both the pre and post-natal periods. Various factors including socio-economic status (SES) have been identified from studies as risk factors that are associated with FAs in children. Generally higher SES has been correlated with improved health outcomes, however, in respiratory allergies higher SES may be associated with higher prevalence. With regards to SES as a risk factor for food allergy development, literature has indicated evidence of a relationship between SES and allergies but with conflicting results of both high and low SES postulated as risk factors. Methodology: This study is a sub-study of the South African Food sensitisation and Food Allergy (SAFFA) study, an on-going cross-sectional, observational study of IgE-mediated food allergy in an unselected population of children aged 12-36 months. The aim is to explore the influence of SES on food sensitisation and food allergy prevalence in children. We used a variety of measures of SES including household size, parental education, employment status and household income to investigate the association between SES and food allergy prevalence using sensitisation, self-reported respiratory and skin allergy and challenge proven food allergy data from children across the urban Cape Town Metropole. Associations between the SES variables and sensitisation/allergy were assessed using the Z-test for proportions and Chi-square/Fisher's exact. Part A comprises the protocol which describes the methodology of the research. Part B is the review of literature on food allergy prevalence and risk factors associated with food allergy development. Section C presents the "journal ready" manuscript according to the requirements of the Annals of Allergy, Asthma & Immunology Journal (Appendix 3). Results: The prevalence of low level sensitisation (at Skin Prick Test (SPT) ≥1mm) to any food was 12.3%, medium level (at SPT≥3mm) was 9.6%, high level (at SPT≥7mm) was 4.5% and challenge proven IgE mediated FA was 2.4%. Of the total 739 participants in the sample, 91 were sensitised to 1 or more foods. A trend of increased sensitisation at SPT≥1mm, ≥3mm, ≥7mm and proven food allergy in children of parents with tertiary education was observed (14.8%, 11.9%, 5.8% and 2.9%) compared to parents who attained primary/secondary education (10.5%, 7.9%, 3.5%, and 2.1%) respectively though these results did not reach statistical significance. Highest risk for food sensitisation (FS) and FA were in children with parents who are employed (p=0.03) and in children who are from homes with higher household income (p=0.02). Household size showed no association with FS and FA. No significant differences in sensitisation patterns were noted between ethnic groups. Conclusion: The analysis showed an existing burden of IgE mediated FAs in South African children advocating for diagnosis and management. SES is associated with food allergy in young children with a positive relationship to parental employment status and income.